sejam as funçoes f(x) = x² -2x + 1 e g(x) = 2x + 1 a) g(f(x)) b)g(f(2)) c )f(f(1))
Soluções para a tarefa
Respondido por
0
f(x) = x² -2x + 1 e g(x) = 2x + 1
a) g(f(x)) = 2(x² -2x + 1) + 1 ==> 2x² - 4x + 2 + 1 ==> 2x² - 4x + 3
==================================================
b)g(f(2)) = 3
f(2) = 2² - 2(2) + 1 ==> 4 - 4 + 1 ==> 1
g(1) = 2(1) + 1 ==> 2 + 1 ==> 3
===================================================
c )f(f(1)) = 1
f(x) = 1² - 2(1) + 1 ==> 1 - 2 + 1 = 0
f(f(x)) = 0² - 2(0) + 1 ==> 0 - 0 + 1 = 1
Perguntas interessantes
Matemática,
8 meses atrás
Matemática,
8 meses atrás
História,
1 ano atrás
Geografia,
1 ano atrás
Biologia,
1 ano atrás
Artes,
1 ano atrás